2019
DOI: 10.2224/sbp.8141
|View full text |Cite
|
Sign up to set email alerts
|

Online life insurance purchasing intention: Applying the unified theory of acceptance and use of technology

Abstract: We developed and examined a theoretical model to explain the key factors influencing Chinese customers' purchasing intention of online life insurance. The proposed theoretical model incorporated the unified theory of acceptance and use of technology (UTAUT) with 2 external factors: online trust and perceived risk. SmartPLS 2.0 was used to analyze the data collected from field survey questionnaires (N = 315). The results showed that customers' online life insurance purchasing intention was significantly impact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
1
7
0
2
Order By: Relevance
“…The value below 0.90 is proposed to establish the discriminant validity (Aziz et al, 2019). The previous study (Iglesias et al, 2019;Jiang et al, 2019aJiang et al, , 2019b tested discriminant validity based on the metrics from the Fornell-Larcker criterion and suggests that this measure is not proper for accessed discriminant validity evaluations. Thus, HTMT is used to test the discriminant validity of this study.…”
Section: Measurement Modelmentioning
confidence: 99%
“…The value below 0.90 is proposed to establish the discriminant validity (Aziz et al, 2019). The previous study (Iglesias et al, 2019;Jiang et al, 2019aJiang et al, , 2019b tested discriminant validity based on the metrics from the Fornell-Larcker criterion and suggests that this measure is not proper for accessed discriminant validity evaluations. Thus, HTMT is used to test the discriminant validity of this study.…”
Section: Measurement Modelmentioning
confidence: 99%
“…As noted in most medical care services reforms, customers’ perceptions and purchase intention (Jiang et al, 2019; Wu et al, 2008) are the pillars of healthcare insurance policy objectives. Customers’ intention to purchase health insurance, which involves value judgment of fairness (Yu et al, 2008) based on the degree of purchase intention, was examined in this study by including a determinant, insurance literacy, into the Theory of Planned Behavior (TPB).…”
Section: Introductionmentioning
confidence: 99%
“…Both the Chinese version and the English version were provided to fit the needs of all respondents. Some items have been adapted from previously validated instruments in the existing studies ( Davis, 1989 ; Venkatesh et al, 2003 ; Slade et al, 2015 ; Jiang et al, 2019 ; Singh et al, 2020 ; Batucan et al, 2022 ; Nan et al, 2022 ). The corresponding statements were modified to suit the current research theme.…”
Section: Methodsmentioning
confidence: 99%
“…For example, according to the literature review presented by Utami et al (2021) , the positive relationship is mostly robust regarding the adoption of FinTech products. Jiang et al (2019) revealed that social influence has a significant positive impact on intention to purchase online life insurance using a sample of 315 participants in China. Keat et al (2020) reported the same result using a sample of 183 engineering students in Malaysia.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation